Aplikasi Perhitungan Kebutuhan Zat Gizi Pada Penyakit Diabetes Berbasis Android - Prasetyo, Endro Dwi; , Dedi Gunawan S.T., M.Sc (2016)
Diabetes is a chronic disease that happens when the pancreas doesn't produce enough insulin and is a degenerative disease that many suffered by modern people with unhealthy diets. The calculations for the nutritional intake of patients with diabetes mellitus are still using manual calculations. so that the process of calculating the nutritional intake of every patient with diabetes mellitus takes a long time. while based on a survey of patients with diabetes mellitus by Indonesia Health Department there are 8.4 million patients every years. In this study will be develop a system to calculate the nutritional intake of patients with diabetes mellitus based by android at PandanArang Boyolali Hospital. Android is a platform that has become one of the most popular operating system with millions of new users every year. The development of this system using PERKENI basic calculation formula that is used to calculate nutritional needs for specific patients with diabetes mellitus, and the test results showed that 87 % of respondents from the ranks of nutritionists responded well and the application is proven to facilitate the work of dietitians in calculating the nutritional intake of patients with diabetes mellitus.